Human milk metabolome is associated with symptoms of maternal psychological distress and milk cortisol - Kortesniemi Maaria; Slupsky Carolyn M.; Aatsinki Anna-Katariina; Sinkkonen Jari; Karlsson Linnea; Linderborg Kaisa M.; Yang Baoru; Karlsson Hasse; Kailanto Henna-Maria (Elsevier, 2022)
The composition of human milk is subject to considerable variation, but the effects of maternal stress are largely unknown. We studied differences in human milk metabolome between Finnish mothers (n = 120, secretors) with symptoms of prenatal symptoms of psychological distress and milk cortisol concentrations. Human milk samples acquired at 2.5 months postpartum were analyzed using targeted 1H NMR metabolomics. Self-reported scores for depression (EPDS), overall anxiety (SCL-90), and pregnancy-related anxiety (PRAQ) were used to evaluate psychological distress. Prenatal psychological distress was positively associated with concentrations of short-chain fatty acids, caprate, and hypoxanthine (q < 0.0012). Milk cortisol was positively associated with lactate concentration (q < 0.05). Changes in the human milk metabolome were shown to be associated with maternal psychological distress and concentration of milk cortisol in a dissimilarly, suggesting alterations in bacterial and energy metabolism of the mother, respectively.